A Hermeneutic of Divine Relationship: Implications for the Education and Training of Christian Marriage and Family Therapists. Issue 4 (7th August 2020) - Johnson, Jake
Abstract: This theoretical essay outlines the hermeneutic of Divine relationship, a theological lens through which Christians can develop a deeper appreciation for God's inherently relational nature and desire to be in relationship with all of humanity. In addition to the nature of God, this hermeneutic highlights the nature of human persons, sin and suffering, reconciliation, and hope. In each of these areas, God's love for human creation and humanity's need for intimate relationship are underscored. For marriage and family therapists (MFTs), clinicians who are taught to think about the world in terms of relationships, a hermeneutic of Divine relationship can have profound implications for the ways in which they conceptualize and practice family therapy and engage in personal relationship with clients. Given the significance of this hermeneutic for Christian MFTs, this essay also includes considerations for educating MFTs in matters of Divine relationship and training them to integrate the hermeneutic into their practice of marriage and family therapy.